THE EFFECT OF JUMP ROPE TRAINING ON OXIDATIVE STRESS AND PULMONARY FUNCTION AMONG MEDICAL STUDENTS - Adhyaksa, Afif Fauzi; Ambarwati, Endang; Supatmo, Yuswo; Marijo, Marijo (DIPONEGORO MEDICAL JOURNAL (JURNAL KEDOKTERAN DIPONEGORO), 2020)
Background. Physical inactivity has been known as a global public health problem and also becomes an important risk factor for Non-Communicable Disease (NCD). Jump rope training is an example of aerobic exercise that is easily done with simple tools. It also increases pulmonary function and reduces oxidative stress. The objective of the study assessing the effects of jump rope training on oxidative stress and pulmonary function in male medical students of Diponegoro University. Method. This is a quasi-experimental study with 42 male medical students as subjects. The subjects were chosen purposively and divided into two groups using a matched subject design. The treatment group was given jump rope training for 6 weeks, each week consists of three-session exercises. The control group didn’t perform jump rope training. The pulmonary functions measured are Vital Capacity (VC), Forced Vital Capacity (FVC) and Forced expired volume in one second (FEV1) using spirometry, while the oxidative stress level used malondialdehyde (MDA) parameters measured using the thiobarbituric reactive substances method (TBARS). Paired t-test, independent t-test, Wilcoxon, Mann-Whitney, and Spearman test were used for statistical analysis. Results. There was a significant difference in spirometry test and MDA level in the jump rope training group compared to the control with p < 0.001. Spearman’s correlation analysis revealed that MDA levels were not correlated with pulmonary function (p > 0.05). Conclusion. Jump rope training may decline oxidative stress and improve pulmonary function in male medical students of Diponegoro University.